2004
DOI: 10.1111/j.1365-2559.2004.02031.x
|View full text |Cite
|
Sign up to set email alerts
|

High microvascular density is correlated with high VEGF, iNOS and COX‐2 expression in penetrating growth‐type early gastric carcinomas

Abstract: Increased MVD in PEN type has an intimate causal relationship to angiogenic factors, high VEGF and iNOS expression. The SUP type, in contrast, has characteristics of low angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 15 publications
3
18
0
1
Order By: Relevance
“…Increased levels of COX-2 have been reported in carcinomas of the colon, stomach, breast, esophagus lung liver, and pancreas. 8,10,[11][12][13][14][15] Cyclooxygenase 2 is important for tumorigenesis because prostaglandins, especially prostaglandin E 2 , affect cell proliferation, differentiation, apoptosis, angiogenesis, and metastasis. 10 Nitric oxide produced by iNOS has been reported to enhance the activity of COX-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased levels of COX-2 have been reported in carcinomas of the colon, stomach, breast, esophagus lung liver, and pancreas. 8,10,[11][12][13][14][15] Cyclooxygenase 2 is important for tumorigenesis because prostaglandins, especially prostaglandin E 2 , affect cell proliferation, differentiation, apoptosis, angiogenesis, and metastasis. 10 Nitric oxide produced by iNOS has been reported to enhance the activity of COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…10 Expression of the genes for COX-2 and iNOS is correlated in human lung, colon, prostate, pancreas, and gastric cancers. [11][12][13][14][15] In an animal model of ESCC, Chen et al 16,17 also reported a correlation between COX-2 and iNOS. However, to our knowledge, there have been no detailed reports mentioning the correlation between COX-2 and iNOS in early-stage human ESCC.…”
mentioning
confidence: 99%
“…VEGF increases cancer cell growth by promoting the cleavage and proliferation of tumor cells by binding to the tyrosinase receptor (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…8c). Both VEGF and iNOS have been linked to promoting tumor cell growth and poor survival in human studies [57,58]. The release of Table 7.…”
Section: Skov·3 Csa Expressing Tumor Cells Have Significantly Reducedmentioning
confidence: 99%
“…Tumor promoting mechanisms of iNOS are likely mediated through the production and activity of NO promoting increased growth of tumor and stromal cells, as well as increasing VEGF and vascular activity [57,58]. iNOS levels present in SKOV-3 CV and WT tumors potentially promote tumor vascularization through induction of VEGF expression in the tumor.…”
Section: C5a Enhancement Of Recruitment and Anti-tumor Effects On Macmentioning
confidence: 99%